2012
DOI: 10.5194/hess-16-2365-2012
|View full text |Cite
|
Sign up to set email alerts
|

MODIS snow cover mapping accuracy in a small mountain catchment – comparison between open and forest sites

Abstract: Abstract. Numerous global and regional validation studies have examined MODIS snow mapping accuracy by using measurements at climate stations, which are mainly at open sites. MODIS accuracy in alpine and forested regions is, however, still not well understood. The main objective of this study is to evaluate MODIS (MOD10A1 and MYD10A1) snow cover products in a small experimental catchment by using extensive snow course measurements at open and forest sites. The MODIS accuracy is tested in the Jalovecky creek ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 23 publications
(25 reference statements)
5
32
0
Order By: Relevance
“…Most of these studies were done using the Terra MODIS daily snow product (MOD10A1). More comprehensive reviews can be found in and Parajka et al (2012). Despite the variety of methods used among these studies, the results led to the same conclusion that Terra MODIS snow cover products have a higher overall accuracy than snow maps derived from VEGETATION or AVHRR.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Most of these studies were done using the Terra MODIS daily snow product (MOD10A1). More comprehensive reviews can be found in and Parajka et al (2012). Despite the variety of methods used among these studies, the results led to the same conclusion that Terra MODIS snow cover products have a higher overall accuracy than snow maps derived from VEGETATION or AVHRR.…”
Section: Introductionsupporting
confidence: 54%
“…9. The snow commission in MODIS products can be due to the effect of forest obscuration (Parajka et al, 2012) because the lower boundary of the snow cover is often situated in forested areas in the Pyrenees. In this study we could detect a deleterious effect of the forests by comparing MODIS products with Landsat over forested areas.…”
Section: Landsat Vs Modis Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Holko and Kostka, 2010), snow cover (e.g. Kostka, 2007, 2008;Holko et al, 2009aHolko et al, , 2011aParajka et al, 2012;Krajčí et al, 2016) and runoff formation (e.g. Holko et al, 2011b;Hlaváčiková et al, 2015) including the response of catchment runoff to rainfall, climate and land use changes (Kostka and Holko, 2003;Kostka, 2009;Bičárová and Holko, 2013;Kostka and Holko, 2007;Holko et al, 2009bHolko et al, , 2012a.…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nmentioning
confidence: 99%
“…As a result of conditions caused by a changing climate, the temporal and spatial changes of snowpacks is the subject of many recent studies (e.g., Artan et al, 2013;Holko et al, 2005Holko et al, , 2011Hood and Hayashi, 2010;Kuchment et al, 2010;Parajka and Blöschl, 2008;Parajka et al, 2012). Analyses of flood changes in Europe (Hall at al., 2014) also indicate changes in spring floods which can be caused by changes in the snow regime especially in snow-dominated regions.…”
Section: Introductionmentioning
confidence: 99%